CRIMINAL LAW POLICIES IN THE USE OF MEDICAL MARIJUANA REVIEWED FROM INTERNATIONAL LAW (STUDI PUTUSAN 111/PID.SUS/2017/PN SANGGAU) - Telaumbanua, Brian Christian; Mulyadi, Mahmud; Leviza, Jelly; Marlina, Marlina (Inspiring Law Journal, 2024)
Marijuana, which is included in the class I narcotics category, has problems regarding the legality of its use in the medical field. These narcotics are often hampered by regulations, state policies and institutions authorized to supervise and distribute them. This research is aimed at analyzing national and international legal policies regarding the use of medical marijuana for health services. The aim of narcotics law policy in the crime of class I narcotics abuse against other people is for the health and legal analysis of a civil servant in Decision Number: 111/Pid.Sus/2017/PN. Sanggau. This research uses a normative juridical research method which is descriptive analytical in nature using primary, secondary and tertiary legal materials collected using library study techniques and analyzed using qualitative data analysis methods. The results of the research show that the legality of marijuana use in the medical sector does not have a definite equation due to Law Number 35 of 2009 concerning narcotics prohibiting the use of marijuana in the health sector, however Law Number 36 of 2009 concerning health provides space for recommendations and supervision and results in he was not given a permit to use marijuana in decision Number 111/Pid.sus/2017/PN. Sanggau. International legal policy in the Single Convention on Narcotic Drugs in 1961 provides opportunities for the creation of marijuana use in the medical field with clear research